Clearance of lipoprotein remnant particles in adipose tissue and muscle in humans. - Karpe, F; Humphreys, S; Samra, J; Summers, L; Frayn, K (1997)
A major proportion of triglycerides in plasma triglyceride-rich lipoproteins (TRL) are removed in peripheral tissues by lipoprotein lipase, and hypothetically a minor proportion can also be removed by whole-lipoprotein particle uptake. This second removal pathway has not previously been directly demonstrated in humans. Simultaneous blood samples were drawn from arterialized blood, a vein draining the subcutaneous abdominal adipose tissue, and a deep antecubital vein of the forearm to provide arterio-venous gradients from blood-draining adipose tissue and muscle in seven male subjects. The men were given a fat-rich mixed meal containing vitamin A and the triglyceride and retinyl palmitate (RP) concentrations were quantified in the plasma. Density gradient ultracentrifugation was used to isolate TRL fractions, in which triglycerides, RP, apoB-48, and apoB-100 were quantified. There was clearance of triglycerides in muscle and adipose tissue and, in addition, removal of RP. By analysis of the TRL subfractions, the RP removal was likely to be confined to the largest chylomicron remnant particles. For the Sf > 400 fraction, the area under curve (AUC) relative to arterial for triglycerides were 79% (66-91%) and 81% (72-89%) in adipose tissue and muscle venous outflow, respectively (each P < 0.02 versus arterial). The corresponding values for RP were 87% (73-101%) and 85% (69-100%), respectively, (each P < 0.05 versus arterial). In the Sf 60-400 fraction there was further uptake of triglycerides, but not of RP. We hypothesize that the periphery could be of importance for removal of the largest chylomicron remnants, as their size might partially exclude them penetrating the fenestrated hepatic sinusoidal endothelium to reach the hepatic chylomicron remnant receptors.